Harry S. Truman and the Cold War Revisionists - Ferrell, Robert H. (Book collections on Project MUSE., 2006)
"Ferrell argues that revisionists are often hasty and argumentative in their judgments, understanding neither the times nor the players. These essays challenge the revisionists' perception of President Harry Truman by going below surface appearances of history to examine how this presidency actually functioned in response to unprecedented problems and crises"--Provided by publisher